2020
DOI: 10.21203/rs.2.13257/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of arsenic stress on 5-methylcytosine, photosynthetic parameters and nutrient content in arsenic hyperaccumulator Pteris cretica (L.) var. Albo-lineata

Abstract: Background: Arsenic toxicity induces a range of metabolic responses in plants, including DNA methylation. The focus of this paper was on the relationship between As-induced stress and plant senescence in the hyperaccumulator Pteris cretica var. Albo-lineata (Pc-Al). We assume difference in physiological parameters and level of DNA methylation in young and old fronds as symptoms of As toxicity.Results: The As accumulation of Pc-Al fronds, grown in pots of haplic chernozem contaminated with 100 mg As kg-1 for 12… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In P. cretica and P. straminea, the decreases were 22% and 39%, respectively. Zemanová et al (2020Zemanová et al ( , 2022 confirmed that soil contamination affected physiological and morphological changes in P. cretica roots, as well as changes in soil quality of the root zone, and the dissolved organic C content decreased with increasing As soil contamination. In contrast to our results, Zhan et al (2018) observed a significant increase in dissolved organic C in the root zone of the phytostabiliser Athyrium wardii in soils contaminated with Cd and Pb.…”
Section: Resultsmentioning
confidence: 71%
“…In P. cretica and P. straminea, the decreases were 22% and 39%, respectively. Zemanová et al (2020Zemanová et al ( , 2022 confirmed that soil contamination affected physiological and morphological changes in P. cretica roots, as well as changes in soil quality of the root zone, and the dissolved organic C content decreased with increasing As soil contamination. In contrast to our results, Zhan et al (2018) observed a significant increase in dissolved organic C in the root zone of the phytostabiliser Athyrium wardii in soils contaminated with Cd and Pb.…”
Section: Resultsmentioning
confidence: 71%